Interbank lending and monetary policy transmission: evidence for Germany - Michael Ehrmann; Andreas Worms (Deutsche Bundesbank, 2001)
This paper presents empirical evidence on the behaviour of interbank lending in Germany after a monetary policy impulse. Our VAR analysis shows that following a monetary contraction, the banking system as a whole attracts additional funds from foreign banks. Whereas small cooperative and savings banks do not seem to directly access the interbank market themselves, they do so indirectly through the head institutions of their sectors, i.e. the savings banks and credit cooperative sector, respectively. The interbank flows within these two sectors allow small banks to access funds that might help them in keeping their loan portfolio relatively unaffected. This may explain why the evidence for a bank lending channel in Germany seems to be weaker compared to other countries, e.g. the US. – – Dieses Papier präsentiert empirische Evidenz zum Verhalten der Interbankkredite in Deutschland nach einem geldpolitischen Impuls. Unsere VAR-Analyse zeigt, dass das Bankensystem als Ganzes nach einer geldpolitischen Kontraktion zusätzliche Mittel von Banken aus dem Ausland aufnimmt. Während kleine Kreditgenossenschaften und Sparkassen nicht direkt auf den Interbankenmarkt zugreifen, tun sie dies indirekt durch die übergeordneten Institute ihres jeweiligen Girosystems, d.h. des Genossenschafts- bzw. Sparkassensektors. Die Interbankströme innerhalb dieser beiden Sektoren erlauben es auf diese Weise kleinen Banken an Mittel zu gelangen, mit deren Hilfe sie die Wirkungen geldpolitischer Maßnahmen auf ihr Kreditportefeuille abfedern können. Dies könnte auch erklären, warum die Evidenz für einen Bankkreditkanal in Deutschland schwächer zu sein scheint als in anderen Ländern, beispielsweise den USA.
Keywords: G21; C32; E52; 330; monetary policy; bank lending channel; interbank market; Geldmarkt; Geldpolitik; Transmissionsmechanismus; Deutschland